High-Temperature Oxidation and Pickling Behaviour of Hsla Steels - Monsalve-Gonzalez, A; Artigas-Abuin, A (Springer New York LLC, 2018)
The high-temperature oxidation behaviour of three boron-containing HSLA steels was studied at 800 and 900 °C in laboratory still-air conditions. At both temperatures, the oxidation rate of the specimens was in accordance with the parabolic rate law and was sensitive to the silicon content when they were oxidized at 800 °C. The chemical composition of the oxide scale was also influenced by the silicon content of the steel. The mechanical behaviour of the oxide scales formed at the metal–oxide interface was also different at each temperature. Finally, the pickling rate and surface quality of the steels depended on the chemical composition of the oxides that formed. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.